2018
DOI: 10.1016/j.ultsonch.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the sonochemical synthesis of PVA/ZrO2-vitamin B1 nanocomposites: Morphology, mechanical, thermal and wettability investigations

Abstract: Poly(vinyl alcohol) (PVA) based nanocomposites (NCs) filled by various weight percent of modified ZrO nanoparticles (NPs) with vitamin B (VB) up to 7wt% were fabricated via ultrasonication method then was cast to thin films. The ultrasonication was applied for the preparation and modification process asan easy, safe and fast method. Ultrasonic was responsible for great homogeneities of NPs into PVA matrix, which could not be achieved by mechanical or magnetically stirring. The creation of polymer NCs and chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…All of the PVA/TiO 2 ‐BSA NC films showed a peak in the range 200–300 nm so that in the pure PVA in this region, this peak corresponded to π→π∗ electron transition of residual CO in the PVA. As it is clear from Figure , the optical absorption of PVA/TiO 2 ‐BSA NC films was higher than pure PVA and a partial red shift was observed because of suitable interactions between TiO 2 ‐BSA NPs with PVA polymer matrix …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…All of the PVA/TiO 2 ‐BSA NC films showed a peak in the range 200–300 nm so that in the pure PVA in this region, this peak corresponded to π→π∗ electron transition of residual CO in the PVA. As it is clear from Figure , the optical absorption of PVA/TiO 2 ‐BSA NC films was higher than pure PVA and a partial red shift was observed because of suitable interactions between TiO 2 ‐BSA NPs with PVA polymer matrix …”
Section: Resultsmentioning
confidence: 90%
“…As it is clear from Figure 15, the optical absorption of PVA/TiO 2 -BSA NC films was higher than pure PVA and a partial red shift was observed because of suitable interactions between TiO 2 -BSA NPs with PVA polymer matrix. 40 The band gap values of pure TiO 2 , TiO 2 -BSA NPs, and PVA/ TiO 2 -BSA NC film 6 wt % were calculated to be 3.6, 3.6, and 4.8 from the eq. (1).…”
Section: Ftirmentioning
confidence: 99%
“…But it is reported that there is an increment in the absorption maxima of poly(PyMMA-co-BMA) coated MS at 252 nm validate the complex formation between the MS and functional polymer. 10,28,29…”
Section: Resultsmentioning
confidence: 99%
“…Uniform dispersion of nanofiller in the polymer matrix is essential for attaining desired enhanced properties. The use of sonication (or ultrasound irradiation) has been attempted by many previous authors to achieve uniform dispersion of nanofiller in the polymer matrix. Mallakpour et al fabricated nanocomposites of poly­(vinyl alcohol) and ZrO 2 nanoparticles by using the ultrasound-assisted solvent casting method. Dhatarwal et al also reported ultrasound-assisted synthesis of poly­(methyl methacrylate)/MMT nanocomposites using the solution casting method.…”
Section: Introductionmentioning
confidence: 99%